Exploring factors that drive adoption of various categories of m-commerce: An emerging market study - Pandey, Shweta (Animo Repository, 2020)
The study examines the factors that drive actual adoption of the four categories of m-commerce, namely content delivery, location-based, transaction-based and entertainment in India. Data was collected from 321 m-commerce users and analysed using structured equation modeling (SEM). The results show that performance expectancy, effort expectancy, facilitating conditions, perceived risk and perceived enjoyment have varied impact, while social influence has a significant positive impact across the four categories. Further, personal innovativeness (PI) has a significant indirect impact on adoption of all the categories. The study adds on to the extant knowledge on m-commerce adoption in India and provides insights for marketers in devising relevant strategies for adoption of varied m-commerce categories. Further, it provides insights on the role of PI in driving adoption of m-commerce. The results from the study are limited to the Indian context and need to be validated across other contexts such as country and service offers suggesting future research opportunities. Future studies can also explore other m-commerce categories such as government services and telemetry services. © 2018 International Management Institute, New Delhi.